2015
DOI: 10.3892/or.2015.3861
|View full text |Cite
|
Sign up to set email alerts
|

miR-218 suppresses cardiac myxoma proliferation by targeting myocyte enhancer factor 2D

Abstract: The role of microRNA-92b-3p (miR-92b-3p) in cardiac hypertrophy was not well illustrated. The present study aimed to investigate the expression and potential target of miR-92b-3p in angiotensin II (Ang-II)-induced mouse cardiac hypertrophy. MiR-92b-3p was markedly decreased in the myocardium of Ang-II-infused mice and of patients with cardiac hypertrophy. However, miR-92b-3p expression was revealed increased in Ang-II-induced neonatal mouse cardiomyocytes. Cardiac hypertrophy was shown attenuated in Ang-II-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Previous studies have already demonstrated that the miR-214 could suppress oncogenesis of bladder cancer by targeting the p53 and DNA damage-regulated protein 1 (PDRG1) ( 35 ), inhibit the progression of hepatocellular carcinoma by regulating β-catenin ( 36 , 37 ), also mediating cell proliferation by targeting ERK ( 38 ), mitochondrial transcription factor A (TFAM) ( 39 ) and ADP-ribosylation factor-like protein 2 (ARL2) ( 40 ). The miR-218 suppresses lung cancer and cardiac myxoma cell growth by reducing myocyte enhancer factor 2D (MEF2D) ( 41 , 42 ), inhibits glioma cells proliferation by inactivation of cyclin D1 ( 43 ) pathway and directly target E2F2 ( 24 ), reduces bladder cancer and esophageal squamous cells proliferation by targeting BMI-1 ( 34 , 44 ). The above evidence supports our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already demonstrated that the miR-214 could suppress oncogenesis of bladder cancer by targeting the p53 and DNA damage-regulated protein 1 (PDRG1) ( 35 ), inhibit the progression of hepatocellular carcinoma by regulating β-catenin ( 36 , 37 ), also mediating cell proliferation by targeting ERK ( 38 ), mitochondrial transcription factor A (TFAM) ( 39 ) and ADP-ribosylation factor-like protein 2 (ARL2) ( 40 ). The miR-218 suppresses lung cancer and cardiac myxoma cell growth by reducing myocyte enhancer factor 2D (MEF2D) ( 41 , 42 ), inhibits glioma cells proliferation by inactivation of cyclin D1 ( 43 ) pathway and directly target E2F2 ( 24 ), reduces bladder cancer and esophageal squamous cells proliferation by targeting BMI-1 ( 34 , 44 ). The above evidence supports our conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies observed that microRNAs, a type of small non-coding RNAs, participate in the regulation of MEF2s, especially in the progression of malignant diseases. miR-218 regulates MEF2D expression by targeting 3’UTR of its mRNA and down-regulation of miR-218 in cardiac myxoma condition can increase MEF2D expression and promote cell cycle progression [ 78 ]. In glioma cells, miR-18a binds with 3'UTR of MEF2D mRNA and negatively regulates its expression [ 79 ].…”
Section: Mef2 Physiological Function and Signal Pathwaysmentioning
confidence: 99%
“…Numerous studies have been performed on the role and related mechanism of miRNAs in numerous different kinds of diseases (9)(10)(11)(12). miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%